Cuban economically active population: a new battle? - Olga Lourdes Vila Pérez (Medisur)
One of the challenges that Cuban society faces today is not only its population´s aging as an objective and natural phenomenon; but the impact of this demographic problem on the economically active population. This category includes persons with appropriate working capacity between 17 years and the retirement age, which is stated in the act No. 24 of Cuban Social Security. Since we support the idea of increasing production and productivity of goods worldwide, and we hold up any initiative to enhance human satisfaction or happiness, it is unprofitable for us not to be able to have millions of persons on condition that they spend their physical and mental capacity in the creation of our wealth. Thus, it is important to be aware of the new approaches regarding social policy, in which health workers have a central role to guarantee an increase in life expectancy, among other benefits.